Empowering women: urging immediate breast reconstruction awareness in Pakistan - Noor, Urwah; Shumas, Muhammad (Journal of the Pakistan Medical Association, 2025)
Dear Madam, Breast cancer remains the predominant malignancy among adult females in Pakistan, constituting 46% of all adult female cancer diagnoses at SKMCH&RC from December 1994 to December 2023.1 Immediate Breast Reconstruction (IBR) is a surgical procedure performed immediately after mastectomy to restore the breast's shape. The global adoption of this procedure has significantly increased due to its substantial benefits, including enhanced body image, boosted self-esteem, and improved psychological well-being. However, despite the prevalence of breast cancer in Pakistan, the adoption of this procedure remains notably low. Fewer than 1% of patients in Pakistan choose IBR, with only two tertiary care cancer hospitals offering this option.2 Current practice in Pakistan often favours delayed reconstruction or no reconstruction at all. This trend is primarily influenced by factors such as the risk of complications, acceptance of body asymmetry, financial costs, and advanced age. Additionally, 62% of patients reported inadequate information about IBR, with some stating that their healthcare provider did not present this procedure as an option.3 Furthermore, socio-cultural factors also influence the low acceptance rate of IBR surgery and complicate the decision-making process for patients. Despite its benefits, familial pressures and religious considerations deter many from choosing IBR and result in a notably low acceptance rate.4 Studies show that patients with higher education and more decision-making autonomy are more likely to opt for IBR, highlighting disparities influenced by education and empowerment.5 These barriers prevent women from making well-informed decisions. The low rate of IBR post-mastectomy underscores the need for comprehensive educational campaigns to raise awareness about its benefits. In addition, it is equally important to focus on training healthcare professionals to ensure accurate and comprehensive information about IBR is readily available. Community support programs, counselling services, and patient advocacy programmes can alleviate fears and uncertainties about IBR, thereby increasing acceptance among eligible patients. Moreover, including IBR in national health insurance schemes and subsidising the cost of these surgeries will reduce the financial burden and ensure equitable access to this vital procedure. Addressing the current shortage of skilled surgeons and enhancing the overall capacity of the healthcare system to provide IBR requires investment in training healthcare professionals in reconstructive surgery. It is critical that these steps be taken immediately to increase IBR accessibility and improve the well-being of breast cancer patients in Pakistan. By tackling these challenges, we can enhance the quality of life for breast cancer patients and ensure they receive optimal care.